Impact of Artificial Intelligence on Purchasing and Procurement in South Korea - Lee, Chung (Global Journal of Purchasing and Procurement Management, 2023)
Purpose: The study sought to analyze the impact of artificial intelligence on purchasing and procurement in South Korea Methodology: The research was conducted entirely on computers. Secondary data, or data that doesn't require actual observation in the field, are the focus of desk research. Because it requires little more than an executive's time, telephone rates, and directories, desk research is generally seen as a low-cost strategy in comparison to field research. As a result, the research used data that had already been collected and reported. This secondary data was readily available via the internet's digital library and scholarly articles. Findings: The results show that the impact of AI on purchasing and procurement is significant. AI is used in automate manual tasks, reducing costs and improve accuracy. It also provides insights into purchasing and procurement processes that have previously been difficult to quantify. AI is a powerful tool that is used to improve the efficiency and effectiveness of the purchasing and procurement process. South Korea is making great strides in the use of AI and the impact it is having on purchasing and procurement is clear. Unique Contribution to Theory, Practice and Policy: Future research in the field of purchasing and procurement may be grounded in the rational economic theory and the resource based view theory. Policymakers, researchers, and academics from all across the world will all stand to gain from this study's findings. Executives in charge of national purchasing and procurement initiatives will also use the study's findings to boost artificial intelligence performance across the board. The research suggests that the purchasing and procurement sector should implement technological policies to boost the effectiveness of their primary operations and activities.